Codifying explicit and tacit practitioner knowledge in community social pediatrics organizations: Evaluation of the first step of a knowledge transfer strategy. (April 2020) - Dagenais, Christian; Dupont, Didier; Brière, Frédéric N.; Mena, Diego; Yale-Soulière, Gabrielle; Mc Sween-Cadieux, Esther
Highlights: The iterative process had helped develop a good understanding of the underlying social community pediatrics model. The promoters of the codification process took into account everyone's comments and views. Participants expressed enthusiasm about the co-construction process. The next stage will be to develop a knowledge transfer plan. A similar participatory process should be followed in developing and implementing the knowledge transfer plan. Abstract: In this article, we the present the evaluation of the first phase of a KT initiative, the codification of the tacit and explicit knowledge of community social pediatrics (CSP) practitioners. As increasing numbers of professionals began working in the CSP field, it became necessary to capture the know-how to make it better understood. This first phase of the initiative took advantage of one of the KM stages, the codifying process that is absent from KT models. The evaluation aim to answer the question: "What is the CSPs practitioners level of familiarity with the codification document, as well as their perceptions of its utility and its contribution to the understanding of the CSP model". The results, show that most respondents had consulted the codification document and were able to describe in detail parts of it. The results also show that they considered it to be a useful and necessary tool to guide practices and helpful in understanding the model. The results of this evaluation is paving the way for the next steps of the KT initiative.